Reference genes for the developing mouse lung under consideration of biological, technical and experimental confounders - Shin, H.; Morty, Rory E.; Sucre, J. M.; Negretti, N. M.; Markmann, M.; Hossain, H.; Krauss-Etschmann, S.; Dehmel, S.; Hilgendorff, Anne (Scientific reports, 2022)
For gene expression analysis, the raw data obtained from RT-qPCR are preferably normalized to reference genes, which should be constantly expressed regardless of experimental conditions. Selection of reference genes is particularly challenging for the developing lung because of the complex transcriptional and epigenetic regulation of genes during organ maturation and injury repair. To date, there are only limited experimental data addressing reliable reference genes for this biological circumstance. In this study, we evaluated reference genes for the lung in neonatal C57BL/6 mice under consideration of biological, technical and experimental conditions. For that, we thoroughly selected candidates from commonly used reference genes side-by-side with novel ones by analyzing publicly available microarray datasets. We performed RT-qPCR of the selected candidate genes and analyzed their expression variability using GeNorm and Normfinder. Cell-specific expression of the candidate genes was analyzed using our own single-cell RNA-sequencing data from the developing mouse lung. Depending on the investigated conditions, i.e., developmental stages, sex, RNA quality, experimental condition (hyperoxia) and cell types, distinct candidate genes demonstrated stable expression confirming their eligibility as reliable reference genes. Our results provide valuable information for the selection of proper reference genes in studies investigating the neonatal mouse lung.